Computed tomography in aneurysmal subarachnoid haemorrhage. Issue 6 (June 1980) - Bell, B A; Kendall, B E; Symon, L
Abstract : The initial CT scans of 76 patients with aneurysmal subarachnoid haemorrhage were reviewed, and the amount of blood visible in the basal CSF cisterns was quantified. The outcome of surgery was found to correlate significantly with the quantity of blood seen on the scan, as did the pre-operative grade of the patient, a history of pre-existing hypertension, and the presence of angiographic vasospasm.